2019
DOI: 10.1101/19009258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Spatio-temporal Approach to Short-Term Prediction of Visceral Leishmaniasis Diagnoses in India

Abstract: Background: The elimination programme for visceral leishmaniasis (VL) in India has seen great progress, with total cases decreasing by over 80% since 2010 and many blocks now reporting zero cases from year to year. Prompt diagnosis and treatment is critical to continue progress and avoid epidemics in the increasingly susceptible population. Short-term forecasts could be used to highlight anomalies in incidence and support health service logistics. The model which best fits the data is not necessarily most use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This procedure is fast but it does not guarantee that the retained model has the best predictive abilities. In practice though, results on simulated data suggest both approaches often give identical results (results not shown), in line with recent observations on incidence forecasting (24).…”
Section: Methodssupporting
confidence: 89%
“…This procedure is fast but it does not guarantee that the retained model has the best predictive abilities. In practice though, results on simulated data suggest both approaches often give identical results (results not shown), in line with recent observations on incidence forecasting (24).…”
Section: Methodssupporting
confidence: 89%
“…For example, a recent study developed models with over 80% accuracy for prediction of Schistosoma mansoni persistent hotspots (defined as failure of a village to reduce infection prevalence and/or intensity by specific thresholds) up to two years in the future in the context of decreasing prevalence (26). In a setting with fairly stable transmission, a sub-district-level study for visceral leishmaniasis reported 85.7% coverage of four-month-ahead 25-75% prediction intervals for case counts (27).…”
Section: Discussionmentioning
confidence: 99%
“…In a statistical modeling study, a short-term forecasting of diseases was proposed with an intention of elimination of VL. The model was based on counting data in space and time for evaluating the population of infected number of humans, vectors and dogs and correlating them with several factors like landscape, climatic and economic factors (Nightingale et al, 2020).…”
Section: Current Status Of Vlmentioning
confidence: 99%